Effects of goal orientation and task complexity on audit judgment performance / Zuraidah Mohd Sanusi, Takiah Mohd Iskandar and June M. L. Poon - Mohd Sanusi, Zuraidah; Mohd Iskandar, Takiah; M. L. Poon, June (UPENA, 2007)
This study examined the predictive effects of goal orientation and task complexity on audit judgment performance. We hypothesized that (a) learning goal orientation would relate positively with audit judgment performance (b) performance-avoidance goal orientation and task complexity would relate negatively with audit judgment performance, and (c) performance-approach goal orientation would interact with task complexity to predict audit judgment performance. Auditors from small-sized and medium-sized audit firms (N = 168) participated in our field study by performing an internal control audit task and completing a questionnaire. Hierarchical regression results indicated that learning goal orientation, performance-avoidance goal orientation, and task complexity related to audit judgment performance in the predicted direction In addition, performance-approach goal orientation interacted with task complexity such that performance-approach goal orientation related positively to audit judgment performance among auditors who performed a low-complexity task but not among those who performed a high-complexity task.